Digital consumption in university students of the Central District in Honduras - Reyes Flores, Luis Gerardo; Mejía Velásquez, Roberto Arturo; Reyes Bautista, Andrea Carolina; Flores González, Iris Sarahi (LACCEI, 2024)
Abstract– Introduction: the study focused on the most recurrent forms of digital consumption in university students aged between 17 and 24 years and in turn determined the validity of the scale used for this purpose. Methods: In the first instance, a descriptive analysis was carried out to identify the main consumption trends grouped into two dimensions, for which a correlation analysis between items was considered and finally an analysis using the Structural Equation Model (SEM) technique to identify the most predominant factor loadings in the configuration of the dimensions used, whose reliability reached an Ordinal Omega = 0.87 and Ordinal Alpha = 0.81, taking as reference a convenience sample of 122 subjects. Result: university students give greater importance to: a) Residential internet service, b) Personal internet service for mobile connectivity and c) Local consumption of online banking application services. The correlation between items through the polychoric correlation reported values ranging between 0.3 and 0.5. On the other hand, the SEM showed an adequate adjustment with 8 of the 9 items, which evidenced higher factor loadings in items 3 and 4 for the first factor and item 8 for the second factor. Conclusion: the interest of young university students ranges from consumption through digital platforms to the consumption of products, local delivery services and video streaming, which are increasingly frequented by them. The questionnaire used reports sufficient consistency to be used in other studies, due to the robustness achieved in the SEM.